Pressure assisted flash sintering of Mn-Co based spinel coatings for solid oxide electrolysis cells (SOECs). Issue 12 (15th June 2021) - Javed, Hassan; Saunders, Theo; Reece, Michael John; Zanchi, Elisa; Sabato, Antonio Gianfranco; Boccaccini, Aldo R.; Smeacetto, Federico
Abstract: Pressure assisted flash sintering was used to process Mn-Co-Cu based spinel coatings, electrophoretically deposited on a Crofer22APU interconnect. This method resulted in highly dense coatings, heat-treated for only a short duration (<10 min) at temperatures lower than conventional sintering temperatures. The electrophoretically deposited coatings showed no delamination or cracks after flash sintering at high heating rates (>200 ° C/min). The high heating rate promoted Cu modified Mn-Co spinel and limited the formation of a Cr-oxide scale on the Crofer22APU substrate. Flash sintering was found to be a promising and time efficient sintering technique to overcome some of the issues related to low coating density and oxide scale formation in solid oxide electrolysis cell conditions.